Pengalaman Belajar Gamelan Soepra dalam Paradigma Pedagogi Reflektif - Benidiktus Candra Pamungkas; Udi Utomo (Institut Seni Indonesia Denpasar, 2022)
Gamelan Soepra is a Javanese Gamelan musical instrument that has a diatonic chromatic scale belonging to SMA Kolese Loyola Semarang. The diatonic gamelan which has various types of instruments can collaborate with modern musical instruments. This gives rise to new musical experiences, especially the experience of learning how to play gamelan for the younger generation. In the reflective pedagogy paradigm (RPP), experience is one of the main elements of learning. This study aims to understand the learning experience of Gamelan Soepra and how the students experience learning Gamelan Soepra. The methods used by the authors in collecting data were observation, interview, and document study. Gamelan Soepra learning provides a direct experience of what Gamelan Soepra is, how to play the gamelan and how to mathet, and how students can open themselves up and practice playing music in groups to produce harmonious music. Students are not only trained in musical competence, but they are also formed to be open, caring, have a conscience, and committed to their choices. This research is expected to be a reference for developing learning methods, especially music learning.